Four Iron Age women from KwaZulu-Natal: biological anthropology, genetics and archaeological context - Steyn, Maryna; Whitelaw, Gavin; Botha, Deona; Vicente, Mario; Schlebusch, Carina; Lombard, Marlize (Southern African Humanities, 2019)
We report further details on four partial human skeletons from KwaZulu-Natal previously selected for genetic analysis. Dating and genetic results indicate that they derived from agriculturist communities of the mid-second millennium AD. Morphological and genetic analysis shows that three individuals were female; identification of the fourth as female comes from genetic analysis only. All four were adults at death, three older adults and one younger. Genetically, all four individuals cluster strongly with Bantu-speaking populations with West African roots, a result supported by craniometric data for the one individual with a complete and well-preserved cranium. All nevertheless display some admixture with Khoe-San populations. We show that three of the women, and probably the fourth, carried genetic resistance to the Plasmodium vivax malaria parasite, while two had some protection against Trypanosoma brucei gambiense-induced sleeping sickness. The unusual rock-shelter burial locations of three of the women suggest that their deaths required ritual ‘cooling’. Lightning and violence are possible causes. We argue that this multipronged approach is necessary for the development of detailed and nuanced understandings of the past and of the individuals who lived in the region centuries ago. KEY WORDS: Physical anthropology, ancient DNA, palaeopathology, Bantu-speaker expansion, Iron Age.